Correlation between agility, lower limb power and performance in a sport-specific test in female volleyball players - Schaun, G. Z.; Ribeiro, Y. S.; Vaz, M. S.; Del Vecchio, F. B. (International Journal of Sports Science, 2013)
To evaluate the general and specific physical performance of female volleyball players. Methods: Eight athletes (22 ± 4.04 years; 175.6 ± 7.24 cm; 71.1 ± 7.07 kg) were evaluated for agility, lower limb power and performed a volleyball-specific test. Data were analyzed using an ANOVA with repeated measures, Pearson correlation and the linear tendency test. Results: Correlations were observed in specific volleyball test variables, and between agility and lower limb power (r = -.77; p = .03). Furthermore, in the specific volleyball test, there was a linear trend of an increase in the trial time, and at the height of attack it was observed a linear trend to decrease (p < 0,05) Conclusions: The general and specific performance are similar to those in the literature; significant correlations were observed and the performance of players decreases during repetition of high-intensity efforts in the sport-specific test.